Holocene ochreous lacustrine sediments within the Famatina Belt, NW Argentina: A natural case for fossil damming of an acid drainage system - Maza, Santiago (2014)
A 44m-thick lacustrine succession of silty-clay banded ochres and subordinated sandstones, and conglomerates (known as the Corral Amarillo Formation) is superbly exposed within the Famatina Belt (Central Andes of Argentina) after deep entrenchment by the present-day Amarillo river due to strong recent uplifting and consequent relative drop in base level. The unusual ochreous-rich succession was produced by natural damming (3.48-3.54 14Ckyr BP) of an acid drainage system linked to the alteration cap of polymetallic deposits. Facies of silty-clay ochre (wet season) and banded ochre (dry season) from the paleolacustrine setting are composed of jarosite+goethite and goethite respectively. Geochemically, these layers record high concentrations of Fe2O3 (25-55wt. %) and trace elements (Cu, Zn, Co, As, and Mo with mean concentrations of 2759; 2467; 109; 375 and 116ppm, respectively). Their origin is inferred from a comparative analysis with the present-day Amarillo river, which has a pH of ~3, (SO4)2- concentrations of ~5000mg/l, and jarosite as the dominant phase, in the upper catchments. Waters downstream have pH values of 3-4.5, (SO4)2- concentrations of ~3000-480mg/l, and schwertmannite as the dominant phase. Thus goethite in the paleolake facies is likely related to schwertmannite transformation by an aging process, whereas jarosite is probably transported from the river but could also be associated with post-depositional formation regulated by variations in grain size and the pore fluid chemistry. The Corral Amarillo Formation offers a Natural model, which may be employed to infer the effect on nature of acid drainage of mineralized areas.